New editor welcome editorial: Respecting the past while moving forward. - Claudio R. Nigg (Bern Open Publishing, 2021)
This is to thank the outgoing editorial team and welcome the new editorial team for Current Issues in Sport Science (CISS), the journal of the sport science organizations of Austria (ÖSG) and Switzerland (SGS). CISS focuses on current issues in our multi- and interdisciplinary field reflected its sections: Biology & Medicine; Biomechanics & Informatics; Movement & Exercise Science; Pedagogy & History; Psychology & Philosophy; Public Health; Sociology & Economics; and Technology. We welcome articles that address timely topics, push the envelope, set the stage, and motivate the science in new and innovative topics.